Data on the identification of protein interactors with the Evening Complex and PCH1 in Arabidopsis using tandem affinity purification and mass spectrometry (TAP–MS) - Huang, He (Data Brief, 2016)
Tandem affinity purification coupled with mass spectrometry (TAP–MS) analysis is a powerful biochemical approach to identify protein–protein associations. Here we describe two datasets generated by a series of TAP–MS analyses to co-purify proteins associated with either ELF3 or ELF4 of the Evening Complex (EC) (“Identification of Evening Complex Associated Proteins in Arabidopsis by Affinity Purification and Mass Spectrometry” (Huang et al., 2016a) [1]) or proteins associated with PCH1, which is a newly identified output of the circadian clock to regulate photoperiodic growth in Arabidopsis thaliana (“PCH1 integrates circadian and light-signaling pathways to control photoperiod-responsive growth inArabidopsis” (Huang et al. 2016b) [2]). We used either ELF3, ELF4 or PCH1 fused to a C-terminal tandem affinity tag (6xHis-3xFLAG) as baits and conducted purifications in various genetic mutant backgrounds. These data are discussed in recent publications [1,2], and are deposited at the ProteomeXchange Consortium via the PRIDE partner repository with the dataset identifier PRIDE: PXD002606 (for EC) and PRIDE: PXD003352 (for PCH1).